FLYPAPER EFFECT PADA DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH PADA KABUPATEN/KOTA DI JAWA TENGAH TAHUN 2011-2012 - Marissa Ayu Saputri; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study aims to (1) provide empirical evidence whether the DAU and revenue affect the shopping area in the District / City of Central Java. (2) To provide empirical evidence which one of the most significant influence on the shopping area between the DAU and PAD in the District / City of Central Java. (3) In order to provide empirical evidence of flypaper What happened in 2011-2012. (4) In order to provide empirical evidence whether the flypaper occur in areas with local revenue (PAD) PAD areas with high or low. The population in this study is the district/town in Central Java in the period of 2011-2012, the number of districts / cities in Indonesia are as many as 29 districts and 6 municipalities. The analytical tool used is multiple linear regression analysis. Based on the results of tests performed can be seen that: (1) PAD and DAU together have a significant impact on regional expenditure. (2) Variable DAU more significant effect on local spending compared with PAD. This proves the existence of flypaper Local Government in response to the DAU and PAD (3) Variable DAUt-1 is more significant effect on local spending compared with PADt-1. It also proves that the flypaper also occur in response to the Local Government and PADt Daut-1-1. (4) whether the fly paper effect happened in the regions which have a high Regionally Original Income or in the other way. The important findings of this research indicate that all regions although have high Regionally Original Income, experienced the flypaper effect.